Konstruksi Realitas Sosial Joko Anwar dalam Mempromosikan Film Pengepungan di Bukit Duri - Laila , Qathrunnnada (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study examines how Joko Anwar constructs social reality through the promotion of his film "Pengepungan di Bukit Duri" (Siege on Bukit Duri) on digital media. Using a descriptive qualitative approach, the researcher analyzed Joko Anwar's posts on Instagram, Twitter, and YouTube. The results indicate that the promotional strategy used was not only informative but also emotional, touching on social issues such as injustice and education. The visual and verbal narratives successfully built public engagement, establishing Joko Anwar not only as a director but also as a public communicator who articulates social values ​​through media.